2015
DOI: 10.1371/journal.pone.0139932
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Chitinophaga pinensis on Plant Cell Wall Glycans and Characterisation of a Glycoside Hydrolase Family 27 β-l-Arabinopyranosidase Implicated in Arabinogalactan Utilisation

Abstract: The genome of the soil bacterium Chitinophaga pinensis encodes a diverse array of carbohydrate active enzymes, including nearly 200 representatives from over 50 glycoside hydrolase (GH) families, the enzymology of which is essentially unexplored. In light of this genetic potential, we reveal that C. pinensis has a broader saprophytic capacity to thrive on plant cell wall polysaccharides than previously reported, and specifically that secretion of β-l-arabinopyranosidase activity is induced during growth on ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 69 publications
2
23
0
Order By: Relevance
“…1b). There was some activity on glucomannan (KGM), but it is perhaps surprising that this was not a more dominant activity, as this is the preferred polysaccharide growth substrate of C. pinensis (13) and is abundant in the wood material. There was also some xylanase activity and some hydrolysis of arabinogalactan.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1b). There was some activity on glucomannan (KGM), but it is perhaps surprising that this was not a more dominant activity, as this is the preferred polysaccharide growth substrate of C. pinensis (13) and is abundant in the wood material. There was also some xylanase activity and some hydrolysis of arabinogalactan.…”
Section: Resultsmentioning
confidence: 99%
“…The type strain Chitinophaga pinensis is a Bacteroidetes species isolated from softwood forest litter, and it belongs to a genus that is considered to be strongly chitinolytic but not cellulolytic (12). We previously demonstrated the growth of C. pinensis and the induction of specific enzymes by larch wood arabinogalactan (13), and more recently we performed a proteomic assessment comparing enzyme secretion during growth on glucose and complex plant ␤-mannans (14,15). We found that the secretion of a selection of carbohydrate active enzymes (CAZymes) was induced in the presence of ␤-mannan, likely via the action of polysaccharide utilization loci (PULs).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…C. pinensis is a Gram-negative bacterium that exhibits potential as to the discovery of novel CAZymes (24,40). This bacterium possesses diverse carbohydrate-active enzymes including 191 GHs that can be classified into 56 different families.…”
Section: A Novel Endo-␤-12-glucanasementioning
confidence: 99%
“…At the time of writing, the genus Chitinophaga comprises 12 recognized species (4). Brazilian soils with sugarcane culture have many species of the Chitinophagaceae family (4, 5), and an isolate from a bacterial consortium degrading lignocellulose isolated from sugar cane soil was used as study material.…”
Section: Genome Announcementmentioning
confidence: 99%